Early elbow osteoarthritis in competitive enduro motorcyclist. (16th June 2020) - Guglielmino, Claudia; Musumeci, Giuseppe
Abstract : This case report speculates that prolonged vibration from enduro off‐road sport is deleterious for the elbow joint. This contribution could also aid sports physicians in better understanding this complex unknown phenomenon. No published data are present in the current literature that demonstrates the correlation between early elbow osteoarthritis in enduro motorcyclist overuse.